A Study on the Removal Characteristics and Mechanism of Phosphorus from Simulated Wastewater Using a Novel Modified Red-Mud-Based Adsorption Material - Wenbao Liu; Qin Zhang; Yanbai Shen; Weichao Li; Sikai Zhao; Qiang Zhao; Yiqun Zhang (Separations, 2023)
In this work, a common third-generation environmentally friendly quaternary ammonium salt disinfectant, dimethyl dioctadecyl ammonium chloride (DDAC), was used as the modifier to achieve one-step rapid preparation of the modified red-mud-based adsorption material under the condition of microwave assistance, and applied it to the adsorption phosphorus in solutions. After the process of this modification, the structure of the red mud (RM) was not changed, and the DDAC modification could provide more adsorption active sites. The adsorption experiments indicated that the novel modified red mud (NMRM) exhibited a good adsorption performance for phosphorus. The adsorption capability of NMRM for phosphorus was significantly enhanced, and was about eight times higher than that of the initial RM. The kinetics model of the pseudo-second-order, which implied that phosphorus was chemically adsorbed on the surface of the NMRM, could accurately represent the adsorption procedure of NMRM. The adsorption equilibrium of NMRM could be better depicted using the isotherm model of Freundlich. It was speculated that the ion exchange might be responsible for the adsorption mechanism of NMRM for phosphorus. Thus, the NMRM is a potential material for the treatment of phosphorus-containing wastewater due to its outstanding adsorption capability.